PENGARUH MODAL SENDIRI DAN MODAL ASING TERHADAP LABA PADA PT. DUTA GEMINI DI MAKASSAR - Hj. Andi Tenri Uleng Akal (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The purpose of this study was to determine the influence of their own capital and foreign capital to profit at PT. Duta Gemini In Makassar. This study used a multiple regression analysis with data processing using SPSS 16 for Windows. The results obtained by the regression equation y = 7.819 to 0.086 X1 + 0.101 X2. The correlation between the variables of equity capital with profits 0.443 and the correlation between the variables of foreign capital with profits 0.497. The coefficient of determination of 29%, which means equity and foreign capital effect on profit of 29%. The results of the t test and F test showed that equity and foreign capital no significant effect on earnings.